The Role of Heat Shock Proteins in Antigen Cross Presentation - Murshid, Ayesha; Gong, Jianlin; Calderwood, Stuart K. (Frontiers in Immunology, 2012)
Heat shock proteins (HSP) are molecular chaperones that can bind tumor antigens (Ag) and mediate their uptake into antigen presenting cells (APC). HSP-antigen complexes are then directed towards the MHC class I pathway through antigen cross presentation as well as to the conventional class II pathway. Mechanisms involved in the uptake of HSP-chaperoned Ag and sorting between these pathways are currently under investigation. The pathways of internalization of HSP-Ag complexes are somewhat different from the mechanisms of uptake previously determined for (unchaperoned) particulate and free soluble antigens. A number of studies show that HSP-facilitated Ag cross-presentation requires uptake of the complexes by scavenger receptors followed by Ag processing in the endosome and loading onto MHC class I molecules in the same compartment. In this review we have examined the roles of HSPs and scavenger receptor SRECI in antigen uptake, sorting, processing and activation of CTL.